Photosensitization Ability of 1,7-Phenanthroline Based Bis-BODIPYs: Perplexing Role of Intramolecular Rotation on Photophysical Properties - Singh V.D.; Singh R.S.; Dwivedi B.K.; Mukhopadhyay S.; Shukla A.; Maiti P.; Pandey D.S. (My University, 2025)
1,7-Phenanthroline based bis-boron dipyrromethenes (bis-BODIPYs) B1 and B2 obtained via small substitutional changes (-Cl/-SCH3) have been described. The effect of restriction of intramolecular rotation (RIR) in emission enhancement in a viscous solvent (glycerol) has been studied besides the vital role of intermolecular interactions scrutinized by X-ray single-crystal studies. The efficiency of intersystem crossing (ISC) in the generation of singlet oxygen (φ ∼19.2% and 56.7%) by photoirradiation using visible light along with distinct photostability has been investigated by 1,3-diphenylisobenzofuran (DPBF) titration studies. The 1O2 generation quantum yield and photosensitizing durability of the bis-BODIPYs have been investigated by photooxidation of 1,5-dihydroxynaphthalene (DHN) in the presence of B1 and B2 as photosensitizers. The pseudo-first-order rate constants for photooxidation reactions and consumption rates of DHN reflected appreciable 1O2 generation quantum yields (φ: B1, 29.0; B2, 57.8%). Density functional theory (DFT) studies showed the distribution of electron density over the dipyrrin moiety. Overall results indicated that these new photosensitizers (PSs) may be very promising in photodynamic therapy of tumors, photobiology, and organic photochemistry. Copyright © 2019 American Chemical Society.